THE OPTIMUM DECISION OF OIL AND GAS PRODUCTION SPREADSHEET MODELLING - Winarto, Rudy; Dinariyana, Anak Agung Bagus (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The optimum revenue of an oil and gas industry is subject to the production volume deliverability and relatively volatile product market price which depends on demand and supply level. Naturally, mature production wells will be dominantly producing water instead of oil and gas, meanwhile, the central processing facilities are having their limited capacity to handle it. This study intends to gain the optimum oil and gas production in mature fields by deciding the opening of well choke valves and considering process facilities limitations as constraints. The model is developed using a simplex LP-based spreadsheet. Three wellhead facilities with a total of forty-seven active producing wells gas, oil, and water data are taken as input parameters. The developed model is validated using the last ten days’ actual production data to identify the error margin consistency, a total of 1,410 data combinations were used. It results in an average error margin of 4.57%-gas and 0.9%-oil. The model could be used as an operator decision reference in opening the well’s choke valve to get the optimum production rate, a minor adjustment might need considering the dynamic process parameter condition. Keywords: optimal production, mature wells, choke valve opening, spreadsheet modeling